Empirical study toward corporate legal compliance and anti-corruption for top construction engineering consulting firms - Chen, Jieh-Haur; Chou, Tien-Sheng; Wang, Jui-Pin; Wong, Qin Rui (Journal of Civil Engineering and Management, 2024)
Enhancing legal compliance towards corporate anti-corruption has become a tendency to assure corporate operation sustainable. Corruption that jeopardizes construction supervision, project management, operation maintenance remains a governance challenge in public construction and procurement. The research purpose is to explore the impact factors for anti-corruption legal compliance towards top 5 engineering consulting companies in the Taiwan construction industry. A comprehensive literature review brings 8 hypotheses based on the Structural Equation Modeling (SEM) involving 28 stems for a 5-scale Likert questionnaire. The pilot survey with 22 effective returns demonstrates the validation for the questionnaire. The comprehensive survey collects 314 valid returns from top engineering consulting firms and proves that 5 out of 8 hypotheses stand. The findings conclude the legal compliance framework and top 5 impact factors: commitment, ethical management policy, organization and responsibility, prevention programs, and legal compliance policy. The contributions lie on (1) the identification and ranking for the impact factors, and (2) establishment of legal compliance framework toward corporate legal compliance and anti-corruption for top engineering consulting firms in the Taiwan construction industry. The legal compliance framework is correspondingly built to present how engineering consulting companies carry out anti-corruption legal compliance to assure corporate operation sustainable.